Analisis Nilai-nilai Pendidikan Karakter dalam Novel Rumah Tanpa Jendela Karya Asma Nadia - Yulianto, Agus; Nuryati, Iis; Mufti, Afrizal (UIN Raden Mas Said Surakarta, Indonesia, 2020)
Character education is the most important asset in human life to shape the character of students. Character values in a novel's literary work can be used to shape the character of students. This study aims to analyze the values of character education in the novel Rumah Tanpa Jendela by Asma Nadia. This research is a qualitative research using descriptive analysis method. Data analysis techniques are carried out through data interpretation, reading the entire data, analyzing in more detail, applying the coding process to be described, restating in the narrative, and interpreting or interpreting data. The results of this study are the values of character education contained in the novel